Sleep disturbance is associated with cardiovascular and metabolic disorders - GRANDNER, MICHAEL A. (2011)
Existing research has demonstrated associations between sleep duration and obesity, diabetes, cardiovascular disease and mortality. Sleep disorders research has shown that sleep apnoea, insomnia and other sleep disorders confer risk for cardiometabolic disease, particularly in the presence of reduced sleep duration. The aim of the present study was to examine the associations between general sleep disturbance, operationalized as ‘difficulty falling asleep, staying asleep, or sleeping too much’ as measured in a large, nationally representative sample, and self-reported history of myocardial infarction, stroke, coronary artery disease, diabetes and obesity. Data from the Behavioral Risk Factor Surveillance System were analysed. Complete data were available for 138 201 individuals. A hierarchical logistic regression analysis examined associations before and after adjustment for demographic, socioeconomic, medical and psychological factors. After adjusting for demographic, socioeconomic and health risk factors, sleep duration was associated with obesity [odds ratio (OR) = 1.18, P < 0.0005), diabetes (OR = 1.18, P < 0.005), myocardial infarction (OR = 1.36, P < 0.0005), stroke (OR = 1.22, P < 0.05) and coronary artery disease (OR = 1.59, P < 0.0005). In fully adjusted models that included physical health, significant relationships remained for obesity (OR = 1.14, P < 0.0005), myocardial infarction (OR = 1.23, P < 0.005) and coronary artery disease (OR = 1.43, P < 0.0005). Sleep disturbance is a significant risk factor for obesity, diabetes, myocardial infarction, stroke and coronary artery disease, and effects for obesity, myocardial infarction and coronary artery disease are the most robust after adjustment. This study demonstrates that sleep disturbance is a novel risk factor that is potentially modifiable. Future research should determine whether sleep intervention could reduce the cardiometabolic consequences of sleep disturbance.